ACSL3 is a potential prognostic biomarker for immune infiltration in clear cell renal cell carcinoma - Zhang, Chiyu; Hu, Honglin; Huang, Ruizhen; Huang, Gaomin; Xi, Xiaoqing (Frontiers in Surgery, 2022)
Objective Long-chain acyl-coenzyme A synthases (ACSLs) catalyze the activation of fatty acid and are often dysregulated in malignancies. The purpose of this research was to figure out the ACSL3's prognostic value and mechanism in clear cell renal cell carcinoma (ccRCC). Methods The expression of ACSL3 in ccRCC was investigated in this work using data from the GEO, TCGA, Oncomine and HPA databases. The expression differences of ACSL3 in the cell lines were further detected by qPCR and Western blot. GEPIA, MethSurv, cBioPortal, and the TIMER were used to perform survival and correlation analysis on ACSL3. GO and KEGG analyses were carried out in R using clusterProfiler and GOplot. Protein-protein interactions (PPI) are constructed from Strings website, and the results were visualized in Cytoscape software. Results The expression level of ACSL3 was significantly reduced in ccRCC tissues, and its mRNA and protein expression were also significantly lower in both renal cancer cell lines. ACSL3 is significantly related to clinical stage, OS, DFS, DNA methylation, and immune-cell infiltration. Conclusion Our findings demonstrated that data mining was capable of eliciting information on ACSL3 levels and its role in genetic regulatory pathways in ccRCC.